Finger Painting untuk Meningkatkan Perkembangan Motorik Halus (Keterampilan Menulis) di Kelas Inklusi MI Amanah - Fadilah, Maulida Nur; Zuhroh, Luthfiatus (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2023)
Fine motor is the fine coordination of small muscles that play a major role. One of the fine motor skills is writing skills. The writing ability of students with special needs is still in low qualification. Efforts to overcome these problems are to use finger painting activities. Finger painting activity is a painting technique with your fingers directly without using tools. Finger painting activities can be carried out and make learning active, innovative, and creative in inclusive classes. The purpose of this study was to find out whether finger painting can affect fine motor development, especially writing skills in students with special needs. To achieve the above objectives, a quantitative research type was used with the pre-experimental method using a one group pre test-post test design. Data collection techniques in this study used observation and measurement of writing skills (pretest-posttest). Then the pretest-posttest results were calculated using the Wilcoxon test. The results of this study showed that the average (mean) pretest and posttest results increased by 36,6. The statistical test results of the Wilcoxon signed ranks test were 0.027 <0.05, meaning that there was an effect of giving finger painting activities to improve fine motor development (writing skills) in the inclusion class.